Transcript Isoforms of SLC7A11-AS1 Are Associated With Varicocele-Related Male Infertility - Sanei-Ataabadi, Nafiseh; Mowla, Seyed Javad; Nasr-Esfahani, Mohammad Hossein (Frontiers in Genetics, 2020)
Oxidative stress is one of the crucial mediators of varicocele-related male infertility. Recently, roles of long noncoding RNAs (lncRNAs) in oxidative stress have begun to emerge, however little is known about their role in male infertility. The aim of this study was to determine the role of lncRNA SLC7A11-AS1 in varicocele-related male infertility. Through a high-throughput bioinformatics investigation, we predicated lncRNA SLC7A11-AS1 might be involved in this type of infertility. Thus, we showed a significant elevation in the expression levels of isoforms 6 and 7 of SLC7A11-AS1 in ejaculated spermatozoa of 25 infertile men with varicocele compared to 17 fertile individuals. We also revealed, significant correlations exist between expression levels of these two isoforms with ROS levels and sperm parameters. Overexpression of SLC7A11-AS1 isoform 6 in testicular-derived carcinoma cell lines (NT2 and NCCIT) resulted in a significant downregulation of SLC7A11 gene expression which consequently decreased glutathione (GSH) levels and concomitantly increased ROS levels and enhanced lipid peroxidation which jeopardized cell survival and promoted cell death. Our finding revealed a potential role of oxidative-related lncRNAs in pathophysiology of male infertility associated with varicocele.